Etats limites plastiques en présence de l’écrouissage isotrope - Chaaba, Ali; Bousshine, Lahbib (European Journal of Computational Mechanics, 2009)
Either in Structural Engineering or Metalworking processes by plastic deformation, the limit analysis is among the direct methods of the plastic collapse assessment. Basing on the kinematical approach in the sense of limit analysis and using finite elements method, the main objective of this work is to deal with large plastic deformations of von Mises’s materials taking into account isotropic hardening. In order to overcome difficulties caused by the non differentiability of plastic dissipation, we adopt a regularization method originally developed for compressible materials. In order to follow up the sequences of large deformations, we have used the sequential limit analysis procedure; it consists in the updating of material properties and geometrical configuration after each sequence.